Analysis of the Behavior of Insider Traders Who Disclose Information to External Traders - Xingxing Cao; Jing Wang; Zhi Yang (International Journal of Financial Studies, 2025)
This paper establishes an insider trading model under market supervision, which includes four types of trading entities: an insider trader, n external traders, noise traders, and market makers. The insider trader voluntarily discloses information to the external traders during the trading process. The research findings are as follows: (1) strengthening market supervision can significantly reduce the insider’s expected profit and increase the external traders’ expected profits; (2) the optimal market supervision strategy is closely related to the number of external traders; (3) the insider trader tends to disclose low-precision information to maximize their profits; (4) the precision of information disclosed by the insider trader and the intensity of market supervision affect price efficiency and the amount of residual information. The research results provide a basis for how the insider trader discloses information to external traders in market supervision and offer a reference for regulatory authorities to formulate differentiated supervision strategies.